Erasable white board with three-layer PET (polyethylene terephthalate) structure and preparation process of erasable white board
By using sodium sulfonate polyester dispersant to surface modification of titanium dioxide, the problems of poor dispersion and poor compatibility in PET polyester are solved, and the mechanical properties and wear resistance of PET materials are improved.
Patent Information
- Application Number
- CN202411701794.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Titanium dioxide has poor dispersion and poor compatibility in PET polyester, which affects the mechanical properties and wear resistance of the material.
The surface modification of the titanium dioxide is carried out by using sodium sulfonate polyester dispersant, and amidation polymerization is used to form a dispersant with sodium sulfonate groups in the molecular chain, improving the compatibility and dispersion of the titanium dioxide with PET.
The dispersion performance of titanium dioxide and the mechanical properties of PET materials are significantly improved, including reducing wear value and improving impact strength and tensile strength, showing good wear resistance.
Smart Images

Figure CN119526866A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyethylene terephthalate, in particular to a three-layer PET structure erasable whiteboard and a preparation process thereof. Background Art
[0002] Writing whiteboard is a common office supply, mainly including enamel board, glass board, polyethylene terephthalate board and the like. Among them, PET polyethylene terephthalate has good mechanical properties, high heat resistance, light weight, and the made writing whiteboard has the advantages of being light and portable. Improving the mechanical strength, wear resistance and other properties of polyethylene terephthalate will help expand its practical application in plastic products such as writing whiteboards. Titanium dioxide is a common white pigment, which is cheap, easy to obtain, non-toxic and pollution-free. It is compounded with plastics such as PET, polypropylene, and polycarbonate to obtain white plastic products. However, titanium dioxide is prone to agglomeration and has poor compatibility with polymer plastic matrices such as PET. Adding it to plastics will affect its mechanical properties. Therefore, the development of high-performance dispersants is a research hotspot. Patent CN103937173B discloses a polyester titanium dioxide masterbatch for label film and its preparation method, which uses PET, titanium dioxide, fluorescent whitening agent, dispersant, etc. as raw materials to improve the dispersibility of titanium dioxide pigment and improve the whiteness and brightness of polyester label film. The present invention aims to improve the dispersibility and compatibility of titanium dioxide and PET polyester by using sodium sulfonate polyester dispersant, and obtain PET material with excellent wear resistance and mechanical properties and its erasable whiteboard. Summary of the invention
[0003] The technical problem solved by the invention is to provide a three-layer PET structure erasable whiteboard with excellent wear resistance and mechanical properties.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is: a three-layer PET structure erasable whiteboard, composed of a wear-resistant modified PET upper layer, a PET middle layer and a PET lower layer, and EVA hot melt adhesive is placed between each PET layer.
[0005] The preparation process of the wear-resistant modified PET layer is:
[0006] (1) Add titanium dioxide to water, disperse by ultrasonic, then add 2-5% of the mass of titanium dioxide sodium sulfonate polyester dispersant, heat to 60-70°C, stir for 2-5h, dry and remove water, and obtain dispersant-modified titanium dioxide.
[0007] (2) Add 100 parts by weight of polyethylene terephthalate and 2-8 parts by weight of dispersant-modified titanium dioxide into a twin-screw extruder, with the temperature of each section being 210-270°C and the screw speed being 100-150 r / min, melt extrusion, granulation, and then compression molding by a molding machine at 10-15 MPa and 250-260°C to obtain a wear-resistant modified PET layer.
[0008] Preferably, the preparation process of the sodium sulfonate polyester dispersant is:
[0009] (1) Add terephthaloyl chloride and 3-hydroxypropionic acid to tetrahydrofuran, stir and then add sodium carbonate aqueous solution dropwise, stir and react at 20-25°C for 3-5h, concentrate under reduced pressure, filter, wash with water and dry, then add to thionyl chloride, stir and react at 60-70°C for 4-5h, concentrate under reduced pressure and dry to obtain 3,3'-(terephthalate) dipropionyl chloride. The reaction formula is:
[0010]
[0011] (2) Add 3,3'-(terephthalate) dipropionyl chloride, sodium ethylenediamine ethanesulfonate, and an acid binding agent to N,N-dimethylformamide, stir and react at 20-35°C for 12-18h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a sodium sulfonate polyester dispersant. The reaction formula is:
[0012]
[0013] Preferably, in (1), the mass of 3-hydroxypropionic acid and sodium carbonate is 88-97% and 103-115% of the mass of terephthaloyl chloride.
[0014] Preferably, in (2), the mass of sodium ethylenediamine sulfonate and the acid-binding agent is 84-102% or 54-64% of the mass of 3,3'-(terephthalate)dipropionyl chloride.
[0015] Preferably, the acid binding agent is triethylamine or pyridine
[0016] The technical effect of the invention is that 3,3'-(terephthalate) dipropionyl chloride and sodium ethylenediamine ethanesulfonate are subjected to amidation polymerization reaction to obtain a novel sodium sulfonate polyester dispersant, the molecular chain of which contains a large number of sodium sulfonate groups and can interact with the surface of titanium dioxide, thereby realizing surface modification and dispersion of titanium dioxide and significantly improving the dispersion performance of titanium dioxide. Meanwhile, the sodium sulfonate polyester dispersant contains terephthalate structural units similar to PET, so that the modified titanium dioxide has better compatibility with PET polyester and is evenly dispersed in a PET matrix, so that the PET layer exhibits a lower wear value, higher impact strength and tensile strength, and has good wear resistance and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the structure of a three-layer PET structure erasable whiteboard. DETAILED DESCRIPTION
[0018] In order to further understand the present invention, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Sodium ethylenediamine ethanesulfonate was prepared according to the method of the journal "Organic Chemistry", Vol. 29, No. 6, 2009, 904-908, and the document "Synthesis and Characterization of Sodium Ethylenediamine Ethylene Sulfonate".
[0020] Add ethylenediamine to a flask, add 28.5% sodium hydroxide solution, heat to 80°C, add sodium 2-chloroethanesulfonate (molar ratio to ethylenediamine is 1:1), react for 4 hours, separate the layers, take the upper yellow viscous material, purify and dry to obtain sodium ethylenediamine ethanesulfonate. The structural formula is as follows:
[0021]
[0022] Example 1
[0023] (1) 20 g of terephthaloyl chloride and 19.4 g of 3-hydroxypropionic acid were added to 400 mL of tetrahydrofuran, and after stirring, 130 mL of an aqueous solution containing 23 g of sodium carbonate was added dropwise, and the mixture was stirred at 20° C. for 5 h, concentrated under reduced pressure, filtered, washed with water, and dried. The mixture was then added to 220 mL of thionyl chloride, and stirred at 60° C. for 4 h, concentrated under reduced pressure, and dried to obtain 3,3'-(terephthalate)dipropionyl chloride.
[0024] (2) Add 5 g of 3,3'-(terephthalate)dipropionyl chloride, 44 g of sodium ethylenediamine ethanesulfonate, and 2.7 g of an acid-binding agent, pyridine, to N,N-dimethylformamide, stir and react at 25°C for 18 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a sodium sulfonate polyester dispersant.
[0025] (3) Add 40 g of titanium dioxide to 600 mL of water, disperse by ultrasonic, then add 1.1 g of sodium sulfonate polyester dispersant, heat to 65 °C and stir for 2 h, dry and remove water to obtain dispersant-modified titanium dioxide.
[0026] (4) Add 1 kg of polyethylene terephthalate and 20 g of dispersant-modified titanium dioxide into a twin-screw extruder. The temperatures of each section are 210°C, 230°C, 260°C, 270°C, 270°C, and 270°C. The screw speed is 150 r / min. Melt extrusion and granulation are performed. The mixture is then passed through a molding machine and compression molded at 10 MPa and 60°C to obtain a wear-resistant modified PET layer.
[0027] Example 2
[0028] (1) Add 20 g of terephthaloyl chloride and 17.6 g of 3-hydroxypropionic acid to 300 mL of tetrahydrofuran, stir, then dropwise add 110 mL of an aqueous solution containing 20.6 g of sodium carbonate, stir at 25° C. for 3 h, concentrate under reduced pressure, filter, wash with water, and dry, then add to 220 mL of thionyl chloride, stir at 70° C. for 5 h, concentrate under reduced pressure, and dry to obtain 3,3'-(terephthalate)dipropionyl chloride.
[0029] (2) Add 5 g of 3,3'-(terephthalate)dipropionyl chloride, 4.2 g of sodium ethylenediamine ethanesulfonate, and 2.7 g of an acid-binding agent, pyridine, to N,N-dimethylformamide, stir and react at 35°C for 12 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a sodium sulfonate polyester dispersant.
[0030] (3) Add 40 g of titanium dioxide to 600 mL of water, disperse by ultrasonic, then add 0.8 g of sodium sulfonate polyester dispersant, heat to 65 ° C and stir for 2 h, dry and remove water to obtain dispersant-modified titanium dioxide.
[0031] (4) Add 1 kg of polyethylene terephthalate and 35 g of dispersant-modified titanium dioxide into a twin-screw extruder. The temperatures of each section are 210°C, 230°C, 260°C, 270°C, 270°C, and 270°C. The screw speed is 100 r / min. Melt extrusion and granulation are performed. The mixture is then passed through a molding machine and compression molded at 15 MPa and 255°C to obtain a wear-resistant modified PET layer.
[0032] Example 3
[0033] (1) Add 5 g of 3,3'-(terephthalate)dipropionyl chloride (prepared in Example 1), 5.1 g of sodium ethylenediamine ethanesulfonate, and 3.2 g of triethylamine, an acid-binding agent, to N,N-dimethylformamide, stir and react at 20°C for 18 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a sodium sulfonate polyester dispersant.
[0034] (2) Add 40 g of titanium dioxide to 800 mL of water, disperse by ultrasonic, then add 2 g of sodium sulfonate polyester dispersant, heat to 70 ° C and stir for 4 h, dry and remove water to obtain dispersant-modified titanium dioxide.
[0035] (3) Add 1 kg of polyethylene terephthalate and 50 g of dispersant-modified titanium dioxide into a twin-screw extruder. The temperatures of each section are 210°C, 230°C, 260°C, 270°C, 270°C, and 270°C. The screw speed is 150 r / min. Melt extrusion and granulation are performed. The mixture is then passed through a molding machine and compression molded at 10 MPa and 260°C to obtain a wear-resistant modified PET layer.
[0036] Example 4
[0037] (1) Add 40 g of titanium dioxide to 700 mL of water, disperse by ultrasonic, then add 1.7 g of sodium sulfonate polyester dispersant (prepared in Example 1), heat to 60° C. and stir for 5 h, dry and remove water to obtain dispersant-modified titanium dioxide.
[0038] (2) Add 1 kg of polyethylene terephthalate and 65 g of dispersant-modified titanium dioxide into a twin-screw extruder. The temperatures of each section are 210°C, 230°C, 260°C, 270°C, 270°C, and 270°C. The screw speed is 150 r / min. Melt extrusion and granulation are performed. The mixture is then passed through a molding machine and compression molded at 15 MPa and 260°C to obtain a wear-resistant modified PET layer.
[0039] Example 5
[0040] (1) Add 40 g of titanium dioxide to 70 mL of water, disperse by ultrasonic, then add 1.4 g of sodium sulfonate polyester dispersant (prepared in Example 1), heat to 70° C. and stir for 3 h, dry and remove water to obtain dispersant-modified titanium dioxide.
[0041] (2) Add 1 kg of polyethylene terephthalate and 80 g of dispersant-modified titanium dioxide into a twin-screw extruder. The temperatures of each section are 210°C, 230°C, 260°C, 270°C, 270°C, and 270°C. The screw speed is 100 r / min. Melt extrusion and granulation are performed. The mixture is then passed through a molding machine and compression molded at 15 MPa and 250°C to obtain a wear-resistant modified PET layer.
[0042] Comparative Example 1
[0043] (1) Add 1 kg of polyethylene terephthalate and 20 g of titanium dioxide into a twin-screw extruder. The temperatures of each section are 210°C, 230°C, 260°C, 270°C, 270°C, and 270°C. The screw speed is 150 r / min. Melt extrusion and granulation are performed. Then, the mixture is passed through a molding machine and compression molded at 10 MPa and 60°C to obtain a wear-resistant modified PET layer.
[0044] Comparative Example 2
[0045] (1) Add 40 g of titanium dioxide to 600 mL of water, disperse by ultrasonic, then add 1.1 g of sodium dodecylbenzene sulfonate, heat to 65 ° C and stir for 2 h, dry and remove water to obtain dispersant-modified titanium dioxide.
[0046] (2) Add 1 kg of polyethylene terephthalate and 20 g of dispersant-modified titanium dioxide into a twin-screw extruder. The temperatures of each section are 210°C, 230°C, 260°C, 270°C, 270°C, and 270°C. The screw speed is 150 r / min. Melt extrusion and granulation are performed. The mixture is then passed through a molding machine and compression molded at 10 MPa and 60°C to obtain a wear-resistant modified PET layer.
[0047] Comparative Example 3
[0048] (1) 5 g of 3,3'-(terephthalate)dipropionyl chloride (prepared in Example 1), 44 g of N,N'-dimethylethylenediamine, and 2.7 g of an acid-binding agent, pyridine, were added to N,N-dimethylformamide, and the mixture was stirred at 25°C for 18 h. Ethanol was added for dilution, the mixture was filtered, washed with ethanol, and dried to obtain a polyester dispersant.
[0049] (2) Add 40 g of titanium dioxide to 600 mL of water, disperse by ultrasonic, then add 1.1 g of polyester dispersant, heat to 65 °C and stir for 2 h, dry and remove water to obtain dispersant-modified titanium dioxide.
[0050] (3) Add 1 kg of polyethylene terephthalate and 20 g of dispersant-modified titanium dioxide into a twin-screw extruder. The temperatures of each section are 210°C, 230°C, 260°C, 270°C, 270°C, and 270°C. The screw speed is 150 r / min. Melt extrusion and granulation are performed. The mixture is then passed through a molding machine and compression molded at 10 MPa and 60°C to obtain a wear-resistant modified PET layer.
[0051] Comparative Example 4
[0052] (1) Add 5 g of terephthaloyl chloride (prepared in Example 1), 44 g of sodium ethylenediamine sulfonate, and 2.7 g of an acid-binding agent, pyridine, to N,N-dimethylformamide, stir and react at 25° C. for 18 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a sodium sulfonate dispersant.
[0053] (2) Add 40 g of titanium dioxide to 600 mL of water, disperse by ultrasonic, then add 1.1 g of sodium sulfonate dispersant, heat to 65 °C and stir for 2 h, dry and remove water to obtain dispersant-modified titanium dioxide.
[0054] (3) Add 1 kg of polyethylene terephthalate and 20 g of dispersant-modified titanium dioxide into a twin-screw extruder. The temperatures of each section are 210°C, 230°C, 260°C, 270°C, 270°C, and 270°C. The screw speed is 150 r / min. Melt extrusion and granulation are performed. The mixture is then passed through a molding machine and compression molded at 10 MPa and 60°C to obtain a wear-resistant modified PET layer.
[0055] Referring to the method of GB / T 17657-2013, the wear resistance of the wear-resistant modified PET layer was tested, and the abrasion value F was calculated according to the following formula: F = (m1-m2) / R×100, where F is the abrasion value (mg / 100r), m1 is the mass of the specimen before abrasion (mg), m2 is the mass of the specimen after abrasion (mg), and R is the number of abrasion revolutions (r).
[0056] The whiteness value of the wear-resistant modified PET layer was tested by an integrating sphere spectrophotometer using the reflection method at a test temperature of 25°C.
[0057] The impact strength of the wear-resistant modified PET layer was tested according to GB / T 1043.1-2008 method.
[0058] The tensile strength of the wear-resistant modified PET layer was tested according to GB / T 1040.1-2018 method.
[0059] The test results are shown in Table 1.
[0060] Table 1: Test results
[0061]
[0062] The wear-resistant modified PET layer of Examples 1-5 has a lower wear value F, higher impact strength and tensile strength, and exhibits excellent wear resistance and mechanical properties. This is because the molecular chain of the sodium sulfonate polyester dispersant contains a large number of sodium sulfonate groups, which can interact with the surface of titanium dioxide, thereby achieving surface modification and dispersion of titanium dioxide, significantly improving the dispersion performance of titanium dioxide, and at the same time, the sodium sulfonate polyester dispersant contains terephthalate structural units similar to PET, so that the modified titanium dioxide has better compatibility with PET polyester, and is evenly dispersed in the PET matrix, so that the PET layer exhibits excellent wear resistance and mechanical properties.
[0063] The titanium dioxide in Comparative Example 1 has not been surface modified, has poor dispersibility, poor compatibility with PET, is easily agglomerated, has a large abrasion value F of the PET layer, and has low impact strength and tensile strength.
[0064] In Comparative Example 2, common sodium dodecylbenzene sulfonate was used to modify the surface of titanium dioxide. The abrasion value F of the obtained PET layer was larger, and the impact strength and tensile strength were lower than those of the embodiments. This may be because the compatibility of sodium dodecylbenzene sulfonate with PET was poor and it was unable to improve the compatibility between titanium dioxide and PET.
[0065] In Comparative Example 3, 3,3'-(terephthalate) dipropionyl chloride and N,N'-dimethylethylenediamine are used for polymerization reaction. The obtained polyester dispersant does not contain sulfonic acid groups and cannot effectively disperse the surface of titanium dioxide. As a result, the dispersibility and compatibility of titanium dioxide in PET are poor, the abrasion value F of the PET layer is large, and the impact strength and tensile strength are low.
[0066] In Comparative Example 4, terephthaloyl chloride and sodium ethylenediamine ethanesulfonate are polymerized to obtain a sodium sulfonate dispersant, which can effectively disperse the surface of titanium dioxide. The abrasion value F of the PET layer is large, and the impact strength and tensile strength are lower than those of the embodiments. This may be because the sodium sulfonate dispersant does not contain terephthalate structural units and has poor compatibility with PET, making it difficult to effectively improve the compatibility between titanium dioxide and PET.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A three-layer PET structure erasable whiteboard, characterized in that: The three-layer PET structure erasable whiteboard is composed of a wear-resistant modified PET upper layer, a PET middle layer and a PET lower layer, and EVA hot melt adhesive is placed between each PET layer; The preparation process of the wear-resistant modified PET layer is: (1) Add titanium dioxide to water, disperse by ultrasonic, then add sodium sulfonate polyester dispersant, heat to 60-70° C., stir for 2-5 hours, dry and remove water, and obtain dispersant-modified titanium dioxide; (2) 100 parts by weight of polyethylene terephthalate and 2-8 parts by weight of dispersant-modified titanium dioxide are added to a twin-screw extruder, melt-extruded, granulated, and then molded by a molding machine to obtain a wear-resistant modified PET layer.
2. The three-layer PET structure erasable whiteboard according to claim 1, characterized in that: The mass of the sodium sulfonate polyester dispersant is 2-5% of the mass of the titanium dioxide.
3. The three-layer PET structure erasable whiteboard according to claim 1, characterized in that: The temperature of each section of the twin-screw extruder is 210-270°C, and the screw speed is 100-150r / min; the pressure during compression molding is 10-15MPa, and the temperature is 250-260°C.
4. The three-layer PET structure erasable whiteboard according to claim 1, characterized in that: The preparation process of the sodium sulfonate polyester dispersant is: (1) Add terephthaloyl chloride and 3-hydroxypropionic acid to tetrahydrofuran, stir, then add sodium carbonate aqueous solution dropwise, stir and react at 20-25° C. for 3-5 hours, concentrate under reduced pressure, filter, wash with water and dry, then add to thionyl chloride, stir and react at 60-70° C. for 4-5 hours, concentrate under reduced pressure and dry to obtain 3,3'-(terephthalate) dipropionyl chloride; (2) Add 3,3'-(terephthalate)dipropionyl chloride, sodium ethylenediamineethanesulfonate, and an acid binding agent to N,N-dimethylformamide, add ethanol to dilute after the reaction, filter, wash with ethanol, and dry to obtain a sodium sulfonate polyester dispersant.
5. The three-layer PET structure erasable whiteboard according to claim 4, characterized in that: The mass of 3-hydroxypropionic acid in (1) is 88-97% of the mass of terephthaloyl chloride.
6. The three-layer PET structure erasable whiteboard according to claim 4, characterized in that: The mass of sodium carbonate in (1) is 103-115% of the mass of terephthaloyl chloride.
7. The three-layer PET structure erasable whiteboard according to claim 4, characterized in that: The mass of sodium ethylenediaminesulfonate in (2) is 84-102% of the mass of 3,3'-(terephthalate)dipropionyl chloride.
8. The three-layer PET structure erasable whiteboard according to claim 4, characterized in that: The mass of the acid-binding agent in (2) is 54-64% of the mass of 3,3'-(terephthalate)dipropionyl chloride.
9. The three-layer PET structure erasable whiteboard according to claim 6, characterized in that: The acid binding agent in (2) is triethylamine or pyridine.
10. The three-layer PET structure erasable whiteboard according to claim 4, characterized in that: The reaction in (2) is stirred at 20-35°C for 12-18h.
Citation Information
Patent Citations
A polyester titanium dioxide masterbatch for label films and its preparation method
CN103937173B
PTT masterbatch and preparation method thereof
CN104845241A
Delustering color master batch based on polytrimethylene terephthalate
CN104861571A
Titanium dioxide pigment dispersant and preparation method thereof
CN108359277A